Simultaneous fault‐tolerant control and disturbance rejection for systems with fault in polynomial form. (24th October 2022) - Jiao, Yu; Pang, Guochen; Mou, Xiaojian; Zhang, Ancai; Qiu, Jianlong; Cao, Jinde
Abstract: This article studies the simultaneous fault‐tolerant control and disturbance rejection for systems with fault in polynomial form. The unknown external disturbance is considered to be caused by the external source system, and the fault can be expressed as a polynomial function of time. Combining the fault observer and the disturbance observer, a controller is designed, which can not only diagnose the fault, but also improve the anti‐disturbance performance. Finally, a numerical example is given to verify the validity of the results.